A Special Representation of Pell and Fermat polynomials - et. al, Parmender (International Journal of Advanced Science and Technology, 2020)
In this we shall we a special representation of this Fermat and Pell polynomials sequence which is defined by a recurrence relation with initial terms. A recurrence relation is very useful to solve many problems in mathematics. Fibonacci polynomials are very useful in mathematics as well as physics. Thinking of famous mathematician Carl Friedrich Gauss (1777– 1855) about number theory: “Mathematics is the queen of all sciences, and Number Theory is the queen of Mathematics.”Recurrence Relation polynomial is very important topic of mathematic many real life problems can be solved by Recurrence Relation polynomials and numbers.In Number Theory [1,2 ] we work on numbers in mathematics many types of numbers for examples Even number, Odd number, prime number, complete square number etc. In Number Theory we want a solution in integers [2,3,7 ]. Many basic theorems have proved in Number Theory. There many representations of Fermat and Pell polynomials in number theory we are also giving a special representation of Fermat and Pell polynomials.